E-Learning Media (Edlink): Utilization Strategies at the Institute of Islamic Religion Bakti Negara (IBN) Tegal - Rizqi Abdillah; Mustaqim; Siti Nur Azizah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to determine the strategies for utilizing e-learning media (Edlink) in the learning process at the Institute of Islamic Religion Bakti Negara (IBN) Tegal. Using a descriptive qualitative research method with data collection through observation, questionnaires, interviews, documentation studies, and literature studies. The sample was taken using the purposive sampling method with 83 respondents. The initial response from students indicates that they are not yet aware that IBN Tegal campus has e-learning media services (Edlink), because so far, during online learning, lecturers have mostly used WhatsApp groups to deliver materials. The data processing results indicate that there are several strategies that need to be undertaken in the utilization of e-learning (edlink), including (1) analyzing the needs of the university by examining internal and external conditions, (2) university policy support which includes the creation of clear implementation regulations and the formation of an implementation team, (3) e-learning management system covering preparation, implementation, monitoring, and (4) human resource development system by conducting training and socialization gradually and comprehensively for lecturers and providing a complete module guide for using edlink.